CREATION OF A SMART EMPLOYMENT TRACKING SYSTEM FOR UNIVERSITY GRADUATES USING AI - Akhmedov B. A.; Dulan J. (Bright Mind Publishing, 2025)
This article explores the development of an AI-based electronic platform for tracking the employment of university graduates. The platform leverages artificial intelligence technologies to collect, analyze, and interpret employment data in real time. By utilizing advanced algorithms, it ensures accurate tracking of career trajectories and provides insights into labor market trends. The study focuses on the platform's potential to bridge the gap between higher education institutions and the job market, enabling universities to adapt their curricula to the evolving demands of employers. The research outlines the methodological framework for platform design and implementation while evaluating its impact on graduate career outcomes.
Keywords: Artificial intelligence, electronic platform, graduate employment, career tracking, higher education, labor market, data analysis, real-time monitoring, Uzbekistan, technical universities.